2017
DOI: 10.1177/0959651817733596
|View full text |Cite
|
Sign up to set email alerts
|

Robust position control of hydraulic manipulators using time delay estimation and nonsingular fast terminal sliding mode

Abstract: A simple and robust tracking controller based on time delay estimation and nonsingular fast terminal sliding mode is proposed for the position control of hydraulic manipulator. The proposed controller does not require the mathematical model of hydraulic manipulator dynamics, which ensures that the method is simple and model free. Two elements, time delay estimation and nonsingular fast terminal sliding mode, are implemented in the proposed controller. Time delay estimation estimates the complex dynamics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…MATLAB R2019b is applied as the simulation platform to track the ideal curve trajectories by using the FETSM, the ETSM [27], the ESM [28] and PID [10] methods respectively. By comparing the error of position tracking of each joint, the effects of the trajectory tracking of the above four control methods are analyzed.…”
Section: Analysis On Trajectory Trackingmentioning
confidence: 99%
“…MATLAB R2019b is applied as the simulation platform to track the ideal curve trajectories by using the FETSM, the ETSM [27], the ESM [28] and PID [10] methods respectively. By comparing the error of position tracking of each joint, the effects of the trajectory tracking of the above four control methods are analyzed.…”
Section: Analysis On Trajectory Trackingmentioning
confidence: 99%
“…As mobile tasks become more complicated, redundant hydraulic manipulators with 7 DOFs, such as electrically driven redundant robots (e.g., CENTAURO and NimbRo [6]), are increasingly required to improve flexibility and dexterity. For example, Kivelä et al [7] from Tampere University in Finland designed an 8-DOF hydraulic manipulator for the International Thermonuclear Experimental Reactor and found that its redundancy feature was beneficial for optimizing the execution of remote handling tasks. Liang et al [8] designed a 7-DOF HRM with seven revolute joints for rescue areas during natural disasters.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, manipulators and vehicle receiving hydraulic actuation constitute a huge global industrial sector [4][5][6]. Hydraulic manipulators are favoured in industry, mining, agriculture and construction work where large actuation forces are required [7][8][9]. For instance, in 2016 the construction business alone sold 0.7 million units of construction machines, while in 2019 the sales of robotic manipulators, including also hydraulic manipulators, reached the level of 0.4 million units.…”
Section: Introductionmentioning
confidence: 99%
“…There is ongoing research on the non-linear control problem of hydraulic manipulators in several engineering tasks [7,[27][28][29][30]. In this paper, a novel non-linear optimal control method is developed for multi-DOF electro-hydraulic robotic manipulators [1].…”
Section: Introductionmentioning
confidence: 99%